Fabrication of piezoelectric Ca-P-Si-doped PVDF scaffold by phase-separation-hydration: Material characterization, in vitro biocompatibility and osteoblast redifferentiation. Issue 5 (1st March 2022) - Gong, Tianxing; Li, Tingyu; Meng, Lisha; Chen, Yadong; Wu, Tao; Zhou, Jingqiu; Lu, Guoxiu; Wang, Zhiguo
Abstract: Native bone is piezoelectric in nature and generates abundant surface charges under mechanical compression, which regulate osteoblast proliferation, differentiation, adhesion, and so on. Poly (vinylidene fluoride) (PVDF) is becoming one of the most popular piezoelectric polymers because of its easy processability and good biocompatibility. Unfortunately, because only the β and γ crystal phases of PVDF have piezoelectricity, post-treatments, for example, polarizing at high temperature, are required to enhance the piezoelectricity of PVDF scaffolds after fabrication. In this study, we reported a phase-separation-hydration method to fabricate a calcium phosphate silicate (CPS)-doped PVDF scaffold. Our method fabricated a better piezoelectric scaffold than native bone without further processing (∼ 3 pC/N vs. 0.7 pC/N). In addition, the scaffold was mechanically compatible (∼ 7 MPa) with the cancellous bone with sufficient porosity (∼ 45%) to facilitate osteoblast infiltration and bone ingrowth. The in vitro biocompatibility analyses proved that the prepared CPS-PVDF scaffold was biocompatible with osteoblast cells and encouraged osteoblast redifferentiation. In conclusion, our results suggest that this CPS-PVDF scaffold is a promising candidate for bone tissue engineering applications. Graphical abstract: Image 1